Why law firms segregate litigation activities?: an incentive theory approach - Silva, Matheus Henrique Recidivi e (2024)
The economic literature on legal fee contracting has traditionally focused on studying incentives for litigation cases. However, this emphasis overlooks the crucial role lawyers play in structuring corporate transactions and drafting contractual agreements to safeguard economic and financial interests. Both litigation (court work) and consulting (transactional work) serve the common goal of legal protection through state enforcement, yet they differ significantly in their workflows. This paper applies the multitask moral hazard model of Holmstrom & Milgrom (1991) to explore how these differences influence law firms internal organisation and their business relationship with clients. In our model, a client (principal) seeks to minimise economic losses associated with legal issues, which can arise from court litigation or neglected legal contingencies in corporate transactions. The client hires a lawyer (agent) to handle both tasks simultaneously, incentivising the lawyer through a variable wage whose value depends on a signal received by the client after work is completed. Our model shows that, as the lawyer faces higher personal costs for effort, he tends to proportionally allocate more effort on the litigation task, in which outcomes are more directly observable and external feedback is more immediate and likely to happen compared to consulting. This allocation aligns with the idea that risk-averse agents prioritise tasks where their efforts yield clearer and more immediate results. In line with the observations of Holmstrom & Milgrom (1991), our analysis suggests that these incentive structures may explain why large law firms historically chose to separate their litigation and consulting departments. The clearer external feedback in litigation allows for stronger performance incentives, whereas the less measurable outcomes in consulting might demand a distinct incentive approach.